Analysis of language policy implementation in basic education - Maponopono, Naledi (School of Languages and Literatures, 2021)
The South African society is plagued with a “complex and fascinating landscape of multilingualism that comprises of eleven official languages post the apartheid era” (Pluddeman et al, 2004: 13-14). The apartheid era saw only “English and Afrikaans recognised as languages of official status across the nation even though indigenous languages existed in the country” (Cakata & Segalo, 2017). The post-apartheid era which commenced in 1994 have been years in which extensive political negotiation and transition have been occurring which have encompassed establishing constitutional rights for indigenous languages in the South African dispensation. This included the choice for “indigenous languages to uses as languages of learning and teaching (LoLT) and being offered as subjects at schools” (Pluddeman et al, 2004: 13, 14). The aim of this study is to focus on language policy implementation practices in basic education with particular reference to a primary school in Western Cape, City of Cape Town as a case study. It seeks to observe the language practices within the school in order to assess the various patterns of implementation and contribute to scholarly debate pertaining to policy implementation across disciplines. The study will analyse the language policy planning in South Africa at large using Ruiz's (1984) three orientations to language planning: language as a problem, language as a resource and language as a right. It seeks to observe the language practices within the school in order to assess the various patterns of implementation and contribute to scholarly debate pertaining to policy implementation across disciplines. The findings of this study aim to assist language planners in developing a language policy framework in basic education which includes strong monitoring and evaluation systems to alleviate problems at the implementation stage of language policies.